Literature Review:Pengaruh Media Komunikasi Terhadap Keamanan Makanan Jajanan Pada Anak Sekolah Dasar - Desti Aulia Ramadhani; Ratih Kurniasari (Peneliti.net, 2022)
The safety food of snack food among school children in Indonesia han begun to experience poisoning which can cause concern for parents and teachers. Given the large number of victims from not guarded snack food, therefore a study was conducted on the safety of snack foods in elementary school schildren. This literature review aims to motivate school children to choose healthy snack foods. The results of the literature review published in the last ten years show that there are changes to the safety of snacks for primary school children using various communication media that have been made by researchers. So, school children can be motivate ini choosing heathy snack foods.